SLC7A11 Reduces Laser-Induced Choroidal Neovascularization by Inhibiting RPE Ferroptosis and VEGF Production - Zhao, Xiaohuan; Gao, Min; Liang, Jian; Chen, Yuhong; Wang, Yimin; Wang, Yuwei; Xiao, Yushu; Zhao, Zhenzhen; Wan, Xiaoling; Jiang, Mei; Luo, Xueting; Wang, Feng; et al. (Frontiers in Cell and Developmental Biology, 2021)
In age-related macular degeneration (AMD), one of the principal sources of vascular endothelial growth factor (VEGF) is retinal pigment epithelium (RPE) cells under hypoxia or oxidative stress. Solute carrier family 7 member 11 (SLC7A11), a key component of cystine/glutamate transporter, regulates the level of cellular lipid peroxidation and restrains ferroptosis. In our study, we assessed the role of SLC7A11 in laser-induced choroidal neovascularization (CNV) and explored the underlying mechanism. We established a mouse model of CNV to detect the expression level of SLC7A11 and VEGF during disease progression. We found the expression of the SLC7A11 protein in RPE cells peaked at 3 days after laser treatment, which was correlated with the expression of VEGF. Intraperitoneal injection of SLC7A11 inhibitor expanded the area of CNV. We examined functional proteins related to oxidative stress and Fe2+ and found laser-induced ferroptosis accompanied by increased Fe2+ content and GPX4 expression in the RPE-choroidal complex after laser treatment. We verified the expression of SLC7A11 in the ARPE19 cell line and the effects of its inhibitors on cell viability and lipid peroxidation in vitro. Application of SLC7A11 inhibitor and SLC7A11 knockdown increased the level of lipid peroxidation and reduced the cell viability of ARPE19 which can be rescued by ferroptosis inhibitors ferrostatin-1 (Fer-1) and liproxstatin-1 (Lip-1). Conversely, SLC7A11 overexpression induced resistance to erastin or RSL3-induced ferroptosis. Moreover, we tested the possible regulatory transcription factor NF-E2-related factor 2 (NRF2) of SLC7A11 by Western blot. Knock-down of NRF2 decreased the expression of SLC7A11. Our study suggests that SLC7A11 plays a key role in the laser-induced CNV model by protecting RPE cells from ferroptosis. SLC7A11 provides a new therapeutic target for neovascular AMD patients.